A história clínica do estudante de medicina da UFSCar - Pedroso, Gustavo Alves (Universidade Federal de São Carlos, 2024)
This work aims to reflect on my development as a physician and individual during my undergraduate studies in Medicine. It will address topics that have proven significant in my personal journey within the framework of a clinical history, as described in the literature, which was one of the main pillars of knowledge acquired during the course. The various stages of my undergraduate studies will be covered in topics as the structure of the clinical history unfolds. Finally, it presents an opinion on how my professional life has been and will be after completing the course.
The clinical history of ufscar medical student
Keywords: Anamnese; Medicina; Narrativa crítico-reflexiva; Estudantes de medicina; CIENCIAS DA SAUDE::MEDICINA::CLINICA MEDICA